Peningkatan Kesadaran Sosial-Religius Pada Remaja Hindu Melalui Keterlibatan Akademisi Di Banjar Buana Sari Desa Stowe Brang, Sumbawa - Dharma, Putu Wisnu Guna; Susanti, I Gusti Ayu Puji; Putri, Ni Made Suardani; Purwanto, Susilo Edi; Anom, Anak Agung Istri (Widya Sandhi, 2025)
This article discusses the strategic role of academics in enhancing the socio-religious awareness of Hindu communities in Banjar Buana Sari, Stowe Brang Village, Sumbawa. The improvement of this awareness involves a youth engagement model through community service activities based on Balinese script literacy, strengthening educational motivation, and training in formulating the articles of association and bylaws of the sekaha teruna youth organization. These initiatives demonstrate a significant impact on the understanding, participation, and internalization of socio-religious aspects among Hindu adolescents.The methods applied include training, lectures, and hands-on practice. The results show an increase in Balinese script literacy skills, successful formulation of the articles of association and bylaws for the sekaha teruna, as well as openness toward improving educational awareness related to Hinduism. The impact of these activities includes a deeper understanding of Balinese script literacy, improved competency in developing organizational documents for Hindu youth groups, and greater awareness of the importance of youth education in creating a better future.